SIFAT FISIK MAKANAN PADAT (FOODBAR) BERBASIS TEPUNG KOMODITAS LOKAL - Nuraisyah, Anni (Jurnal TAMBORA, 2020)
Consumption of fast food continuously can be detrimental to human health. An effective solution is to make innovative food that is able to meet the adequacy of nutrition, one of which is foodbar. The raw materials used in the manufacture of foodbar come from local commodities which are flourished, including sweet potatoes, green beans and Moringa and added porang to unite the three ingredients. Yellow sweet potato flour contains 77.7% carbohydrates with high digestibility (98%), while Moringa leaf flour contains 27.1 grams / 100 grams protein. Mung bean flour is used as a flavoring agent, while porang flour which is rich in glucomannan acts as a binder agent to produce foodbar products that are not easily destroyed. The treatment in this study used two factors, namely the composition of the composite flour and the composition of the addition of porang. Observations made include physical properties including water content, volume expansion, kamba density and texture of the foodbar. The best treatment on the foodbar was the combination treatment of 100 grams of yellow sweet potato flour (40 grams) green bean flour (60 grams) moringa leaf flour and (4%) porang (P3T1).